Implementasi Maqashid Syariah dalam Perniagaan Dropship: Implementation Of Maqashid Syariah In Dropship Commercial - Sidanatul Janah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
The Rapid technological developments have an impact on human activities directly and indirectly. Having a market place makes it easier for a seller to sell their products. Dropship can be interpreted as a business activity that uses small capital. This business does not stock goods like sellers in general. So if a buyer comes to the dropshipper (the person who does the dropshipping), he will contact the party he is working with for the goods. Furthermore, the goods purchased by consumers will be sent directly from the party collaborating with the dropshipper to the consumer. Dropshipping activities can be interpreted almost the same as brokering. In this article we will discuss the scope of dropshipping, the use of wakalah contracts, the use of samsarah contracts, and their correlation with the concept of maqashid Sharia. The research approach used is a qualitative approach in the form of a literature study which leads to providing a description of the research object and its relation to everything being researched in the form of dropshipping in Maqashid Syariah. In this research, a qualitative descriptive design type was used and focused more on library research. The results of this research are that based on Islamic law, dropship activities are related to wakalah contracts and samsarah contracts. Based on analysis using Sharia maqashid, Dropshipping can be carried out as long as it meets the pillars and requirements of Islamic behavior and there is benefit for humans, as well as benefits for both parties.